2015
DOI: 10.15394/jdfsl.2015.1210
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Black Box/Event Data Recorder: Legal and Ethical Perspectives and Challenges with Digital Forensics

Abstract: With ubiquitous computing and the growth of the Internet of Things, there is vast expansion in the deployment and use of event data recording systems in a variety of environments. From the ships' logs of antiquity through the evolution of personal devices for recording personal and environmental activities, these devices offer rich forensic and evidentiary opportunities that smash against rights of privacy and personality. The technical configurations of these devices provide for greater scope of sensing, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…• Law et al (2011): "To enable the protection of data privacy, personal data that are not related to the investigation subject should be excluded during computer forensic examination" (p.1). • Losavio et al (2015): "This highlights the twin challenges of forensic accessibility in these highly mobile devices and the intense privacy concerns which may now accompany the profiles of people in ways never before possible." (p.45).…”
Section: Forensics Investigations Ethical Guidelinesmentioning
confidence: 99%
See 3 more Smart Citations
“…• Law et al (2011): "To enable the protection of data privacy, personal data that are not related to the investigation subject should be excluded during computer forensic examination" (p.1). • Losavio et al (2015): "This highlights the twin challenges of forensic accessibility in these highly mobile devices and the intense privacy concerns which may now accompany the profiles of people in ways never before possible." (p.45).…”
Section: Forensics Investigations Ethical Guidelinesmentioning
confidence: 99%
“…When the investigation is concluded, the report should include details of exactly what was examined, who was included in the investigation, which devices were examined (and who they belonged to) (Losavio et al, 2015), how data was classified as relevant (to be reported), confidential (only to be reported if the court so orders), irrelevant (not to be divulged) and how the data was preserved to prevent any alteration (Saleem et al, 2014;Roux and Falgoust, 2012).…”
Section: Report All Investigative Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…If the event relates to a civil action, then it may be subject to a court order to be produced and examined by an opposing party. This may both enhance the pursuit of truth as to an event at the cost of significant inconvenience to the device holder …”
Section: Legal Guidance Present and Futurementioning
confidence: 99%